Konsep Perkembangan Anak Usia Dini Menurut Perspektif Ibnu Qoyyim Al-Jauziyyah - Taufik, M.; Rahmi, Alfi (ANWARUL, 2023)
The research problem refers to the concept presented by Ibn Qoyyim Al-Jauziyyah regarding Early Childhood Development in the book Only For You My Son, a translation of the book Tuhfatul Maudud Bi Ahkamil Maulud with the aim of knowing how early childhood development according to Ibn Qoyyim Al-Jauziyyah from physical aspects includes the condition of body structure, gross motor skills and fine motor skills. This type of research is library research, collecting data from primary and secondary data sources, data analysis techniques using deductive methods. Based on the researcher's analysis, the results are: 1) The concept of early childhood development according to Ibn Qoyyim Al-Jauziyyah is a process of increasing maturity and psychological function that needs to be considered from various aspects. 2) Characteristics of early childhood development. On the physical aspect which includes body structure, namely the hardening of the baby's bones starting in the early years, the muscles develop slowly during infancy. Gross motor skills aged 0-3 months can hold their head and body upright. Age 3-6 months can lift his head, tilt his body. Age 6-9 months can sit alone and crawl. Fine motor skills aged 0-3 months have a finger grasping reflex when the palm is touched. Age 3-6 months can move toys from right hand to left hand. Psychological development includes religious aspects, introducing the phrase Tawhid La ilaha illallah, Muhammad Rasulullah and motivating children to be diligent in worship, which will have a good influence on their psychological development. Then the moral aspect by keeping children from moral damage such as lying, stealing, clothing that violates the rules of religious values, and the social aspect by keeping children from being lazy so that there is no social interaction, which will have a bad effect on their social development.